Effect of training loads on physiological parameters of soccer players - Campos, Eduardo Zapaterra [UNESP]; Milioni, Fabio [UNESP]; Zanuto, Everton Alex Carvalho [UNESP]; Almeida, Pablo Barreto [UNESP]; Gobbi, Ronaldo Bucken [UNESP]; De Andrade, Vitor Luiz [UNESP]; Junior, Pedro Balikian [UNESP]; Papoti, Marcelo [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this study was to investigate the effects of three weeks of training with intensity monitored on the aerobic capacity of professional soccer players. Fourteen players, members of a first division Brazilian Championship team in 2010, aged 22.78 ± 3.06 years were evaluated pre and post three weeks of training. The anaerobic threshold intensity LAn was determined by bi-segmented method, for this four submaximal efforts of 800 meters with intensities 10, 12, 14 and 16 km/h were applied. Thirty three training sessions were quantified in zones according to heart rate related to the LAn (FC LAn): Z1 - 10% below, Z2 - 90-100% and Z3 - above the FCLAn. During training participants remained 31.17 ± 14.86%, 42.96% and 25.87 ± 14.90 ± 16.67% in Z1, Z2, and Z3 respectively. There were no significant differences in the LAn (pre = 13,29 ± 0,71 kmh-1; post = 12,85 ± 0,90 kmh-1), perceived exertion (pre = 11,53 ± 1,45 u.a; post = 11,23 ± 1,53 u.a) and FCLAn (pre = 166,64 ± 10,69 bpm; post = 174,50 ± 10,89 bpm) between conditions before and after training, indicating that three weeks of training are insufficient to generate positive changes in soccer players LAn.
Efeito das cargas de treinamento sobre parâmetros fisiológicos de futebolistas
Keywords: Anaerobic Threshold; Soccer; Training